PERILAKU BANGUNAN STRUKTUR BETON BERKOLOM MIRING TERHADAP GAYA GEMPA LATERAL - Muhammad Sofyan; RR.Mekar Ageng Kinasti; Abdul Rokhman (Sekolah Tinggi Teknik - PLN, 2017)
The geometry of the building, especially in the column, will affect the response of the structure when the earthquake load works. This study aims to discuss about the drift and inter-story drift of the Story buildings structure sloped due to lateral earthquake loads and ductility. The case under consideration is a three-dimensional Frame 10 story. Where will be designed 3 types of concrete structure building systems. These three 3D frame systems will be analyzed and compared their performance against earthquake loads by using computer program aids. The results of this research when Improved Peak ground acceleration (PGA) values ranging from 0.8g 1.2g to 1.5g show that Model 2 (HSB-2) has the largest drift (drift) or it can be said to have the smallest stiffness among the others. After analyzing the pushover on the building reviewed then got the ductility value of building model 1,2 and 3 respectively is equal to 1.75; 1.711; And 1.686. In terms of Ductility, HSB-1 Building has the best performance among the others.